RELATIONSHIPS AMONG READING ANXIETY, READING SELF-EFFICACY, AND READING COMPETENCY IN THE VOCATIONAL HIGH SCHOOL IN SINGARAJA - Trisnayanti, Ni Luh Putu Devi; Agustini, Dewa Ayu Eka; Tantra, Dewa Komang (Universitas Pendidikan Ganesha, 2020)
The general objective pursued is to describe and to relate the students’ reading anxiety, reading self-efficacy to their reading competency in the Vocational High School in Singaraja. The design applied is a quantitative research. There were 90 students recruited using cluster quota sampling. The data were gathered using scales and reading test. The obtained data were analyzed in two phases: descriptively and inferentially. Whereas inferentially, the data were analyzed using pair-wise correlation and multiple correlation technique. The findings show that: 1) the students’ reading anxiety is at high level while reading self-efficacy and reading competency are at the low levels; 2) the relations pair-wisely are negative and positive significantly correlated; and 3) the simultaneous or multiple relationships of the reading anxiety and reading self-efficacy to the students’ reading competency is proven to be significant ( =0.81; α =0.01).